PENDARAHAN BERULANG SETELAH 14 TAHUN PADA MALFORMASI ARTERIOVENA DI SEREBELARIS - Ni Nyoman Ayu Trisnadewi,* Kumara Tini* (Neurona Majalah Kedokteran Neuro Sains, 2018)
ARTERIOVENOUS MALFORMATION AVM A FORM OF ABNORMALITY IN BRAIN VASCULARIZATION IN THE CEREBELLUM IS A RAREDISORDER THE RISK OF RECURRENT BLEEDING AFTER INITIAL EPISODE AT FIVE YEARS IS VERY LOW ABOUT 367 WE REPORTED A CASE OF25 YEARSOLD MAN WITH HISTORY OF RECURRENT BLEEDING AFTER 14 YEARS WITH HYDROCEPHALUS AS COMPLICATION